Social Inclusion in Building Islamic Positive Behavior on ADHD Children - Mierrina Mierrina (Indonesian Psychological Research, 2019)
This research aimed to know the effect of social inclusion program education in improving Islamic positive behavior in ADHD children. The subjects were children with ADHD tendencies, in one of the inclusion Kindergarten School in Sidoarjo. The research was experimental study with single subject or known as Single Case Design or SGD, with plural baseline design between variables (multiple baseline cross variables). It aimed to see the differences in Islamic positive behavior shown by ADHD children in baseline conditions (A) with intervention condition (B). Positive Islamic behavior, including the aspects of aqeedah and moral, had three variables for each aspects; â€œsalamâ€, â€œBismillahâ€ and â€œAlhamdulillahâ€ for aspect of aqeedah. While â€œpleaseâ€, â€œpatienceâ€ and â€œlove friendsâ€ for aspect of moral or noble character. The result showed that education and intervention provided to the subjects were quite able to increase the positive Islamic behavior of the subject in a positive direction. From the aspect of aqeedah the pronunciation of "salam" and "Bismillah" showed a significant change, for the pronunciation of "Alhamdulillah" showed a slight change, between the baseline and intervention condition. In the aspect of noble character, it was also sufficient to show significant changes to "please" and "be patient, while to" love friends "had not shown a significant change, between baseline conditions and intervention conditions. The influence of social inclusion program education had significant influence on increasing Islamic positive behavior in ADHD children, which indicated more by teacher and peer contributions, while parents did not show positive contributions due to lack of emotional attachment between subjects and parents, especially mothers.